KARAKTERISASI PATI DARI BATANG KELAPA SAWIT YANG TELAH TIDAK PRODUKTIF - Hidayani, Tengku Rachmi (Politeknik ATI Padang, 2017)
Research on the extraction of starch from unproductive palm oil rods to utilize unproductive palm oil waste into useful materials. This study consists of three stages. The first stage is making sample preparation. The second stage is the process of starch extraction. The last stage is the characterization of starch from the oil palm rod obtained. The characterization of starch yield obtained was analyzed by functional group with FTIR test and thermal characteristic analysis by DTA test. The results showed that the starch of the palm oil rods produced has a good character where the FTIR results show the specific groups for starch and DTA results according to the decomposition point of starch that is at the temperature of 408oC.